2013
DOI: 10.1016/j.jdeveco.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Media exposure and internal migration — Evidence from Indonesia

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 48 publications
1
45
1
2
Order By: Relevance
“…In fact, the lack of information available to people coming from rural areas and the limited opportunities, in terms of labor market prospects open to them, may prevent such people from moving internally to urban areas or internationally [58,59,62]. How the amount of available information affects internal migration patterns in Indonesia is an issue tackled by [63].…”
Section: Climate Shocks and Internal Migrationmentioning
confidence: 99%
“…In fact, the lack of information available to people coming from rural areas and the limited opportunities, in terms of labor market prospects open to them, may prevent such people from moving internally to urban areas or internationally [58,59,62]. How the amount of available information affects internal migration patterns in Indonesia is an issue tackled by [63].…”
Section: Climate Shocks and Internal Migrationmentioning
confidence: 99%
“…15 Second, we use a more flexible specification for installing landline phones in the future and past, that is, replacing our regressor of interest ( Table 5, we find similar patterns in outmigration between treatment and control groups before the installation of landline phones, but they diverge right after the installation. Furthermore, we test whether the post-installation coefficients are different from pre-installation ones, the F statistic for the joint test is 2.74, and we can reject the null hypothesis that all the post-treatment coefficients 15 As a rough but important additional test, we also exclude "Tele" in the same regression, and find that "landline phone anticipator" still remains statistically insignificant (the results are available upon request).…”
Section: Robustness Checksmentioning
confidence: 96%
“…But better information does not uniformly encourage migration-it depends on whether potential migrants over-or under-estimate the prospects of the potential destinations. If potential migrants over-estimate their employment and life prospects in the destination region, better access to information may decrease migration, as found by Farre and Fasani (2012).…”
Section: Introductionmentioning
confidence: 97%
“…During its infancy, the content broadcast by media was stringently controlled by the government. A study by Sanyoto () concluded that the media “had to be hostile to dissidents and critics, and portray them as detrimental to state security.” TVRI was expected to contribute to the unity of Indonesia and to Indonesia's growth as a nation (Farré & Fasani, ). Press council and journalists were also under tight control, through the licensing system, among other constraints.…”
Section: Country Contextmentioning
confidence: 99%